Understanding the organisational cultural elements that impede the success of a Business Process Management (BPM) in South African State-Owned Enterprises (SOEs): A Scoping Review - Makamba, Vuyolwethu; Salamntu Lumka, P. T. (Journal of Islamic, Social, Economics and Development, 2024)
Business Process Management (BPM) is defined as a body of methods, techniques, and tools used to identify, discover, redesign business processes to optimise business processes. In organisations it has been adopted to enhance operational and service efficiency and effectiveness. Despite its recognized potential, the success of BPM within South African State-Owned Enterprises (SOEs) has faced significant challenges. Culture has consistently been cited as a primary impediment to the BPM success in organisations. Culture is complex, necessitating a focused examination of specific organisational cultural elements. This scoping review seeks to understand the organisational cultural elements that impede the success of BPM. A PRISMA-ScR checklist, and a search string was applied using an eligible criterion across three databases. A final of fifteen set of articles were selected using the Rayyan web-based tool, which assisted in screening the large volumes of literature. All the articles that did not meet the eligibility criteria were excluded. To guide the categorising of the organisational cultural elements themes a Schein’s organisational culture framework was used. The emerged themes were categorised into the three levels as recommended by Schein: artifact, espoused values, and the basic underlying assumptions. The most prominent organisational cultural elements that impedes BPM success in the SOEs were hostile and riddled work environment that is full of politics and poor corporate governance. Additionally, poor leadership and incompetence due to lack of adequate skills were also found to be the cultural impediments. Future studies can focus on strategies to address the cultural impediments in SOEs and foster a conducive environment for BPM success